The effect of population size on urban heat island and NO2 air pollution: Review and meta-analysis - Yufei Wei; Rémi Lemoy; Geoffrey Caruso (City and Environment Interactions)
Urban heat island (UHI) and nitrogen dioxide (NO2) concentration in the air are two significant health hazards arising from urbanization. While much research has focused on the local urban context and micro-conditions for sources and exposures in particular case-studies, the effect of the overall level of urban agglomeration, as measured by population size, remains underreported. We compile the literature that explicitly discusses the relationship between UHI or NO2 and population size. We synthesize methods and findings qualitatively, then perform a quantified meta-analysis using comparable data from the corpus. We find that the corpus from which population size effects can be retrieved is very thin given the level of urbanization trends and the health impact. Despite a variety of functional specifications, data gathering processes, and metrics, the literature generally agrees on a significant effect of population size on both UHI and NO2. After pooling data we estimate that each 10-fold increase in population, increases the temperature gap between the city and countryside by almost 2 °C or a 40 % increase when cities get very large. We find that NO2 scales similarly, with a 40 % increase in concentration each time the city population is multiplied by 10. These numbers represent very important health threat given the current urbanization rate and the distribution of city population sizes. We also call for more studies to be conducted, across larger sets of cities, using observed data at higher resolution and comparable city definitions.